2021
DOI: 10.3390/e23121664
|View full text |Cite
|
Sign up to set email alerts
|

CGHS Black Hole Analog Moving Mirror and Its Relativistic Quantum Information as Radiation Reaction

Abstract: The Callan–Giddings–Harvey–Strominger black hole has a spectrum and temperature that correspond to an accelerated reflecting boundary condition in flat spacetime. The beta coefficients are identical to a moving mirror model, where the acceleration is exponential in laboratory time. The center of the black hole is modeled by the perfectly reflecting regularity condition that red-shifts the field modes, which is the source of the particle creation. In addition to computing the energy flux, we find the correspond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Therefore, we now turn to the self-force, [ 18 , 19 ]; we find it convenient to dub this the ‘Feynman power’ [ 17 ]. This is an analogous ‘self-force measure’ as a function of retarded time u : Unlike the Larmor power, the Feynman power can be negative.…”
Section: Feynman Powermentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we now turn to the self-force, [ 18 , 19 ]; we find it convenient to dub this the ‘Feynman power’ [ 17 ]. This is an analogous ‘self-force measure’ as a function of retarded time u : Unlike the Larmor power, the Feynman power can be negative.…”
Section: Feynman Powermentioning
confidence: 99%
“…The Lorentz invariance cross-over is present in the quantum Lorentz–Abraham–Dirac (LAD) force discovered by Ford and Vilenkin [ 19 ] (for a derivation see [ 18 ]), the magnitude of which is a Lorentz scalar invariant jerk where the prime denotes a derivative with respect to proper time. For convenience, this is compared to the classical LAD self-force with scalar magnitude, as we have seen: These are quantum and classical forces (and power), tying together mirror and electrons in close analogy.…”
Section: Bogoliubov Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…Accelerating mirrors can be considered as an analogue of the dynamical Casimir effect in (1+1) dimensions [34,35], a prototype for black hole evaporation [36][37][38][39][40]. It has been observed that there is a strong connection between accelerating mirrors and black hole physics [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%